Household air pollution exposure and risk of tuberculosis: a case–control study of women in Lilongwe, Malawi - Kenneth Maleta; Robert Krysiak; Irving Hoffman; Sam Phiri; Pamela Jagger; Ryan McCord; Anna Gallerani; Charles Jumbe; Joseph Pedit (BMJ Public Health)
Introduction Globally, 3–4 billion people rely on solid fuels for cooking, and 1 billion use kerosene to light their homes. While household air pollution (HAP) emitted from burning these fuels has well-established links to numerous health outcomes, the relationship between active tuberculosis (TB) and HAP exposure remains inconclusive.Methods We explore the association between HAP exposure and TB among adult women in Lilongwe’s high-density suburbs using hospital and community-based health data, objectively measured exposure to HAP, and sociodemographic data controlling for individual, household and community-level confounders. Only one other study combines public health, exposure and sociodemographic data to explore the association between HAP and TB. We report results from a case–control study of 377 primary cooks (76 cases; 301 controls) on the association between risk of developing active TB and HAP exposure. We calculate ORs for developing active TB using indicators of HAP exposure including primary fuel used for cooking, cooking location and frequency of kerosene use for lighting, and in a subset of households, by directly measured cooking area and personal exposure to fine particulate matter (PM2.5) and carbon monoxide.Results We are unable to find an association between self-reported cooking with solid fuels and TB in our sample; we do find that increased frequency of kerosene use for lighting is associated with significantly higher odds of TB. Household area PM2.5 concentration is the only direct HAP measure associated with significantly higher odds of TB. We find that 16.8% of the relationship between TB and kerosene use is mediated by increases in area PM2.5.Conclusion Our findings suggest that efforts to reduce the risk of active TB within the home environment should include strategies to reduce or eliminate kerosene, commonly used for lighting and cooking in many low-income country settings.